EXOGENOUS PLANKTON AS FOOD FOR INTENSIVE REARING OF ORNAMENTAL CYPRINID, EPALZEORHYNCHUS FRENATUS - P. Jha (Archivos de Zootecnia, 2010)
To explore the effect of different management regimes for probable intensification of rainbow shark (Epalzeorhynchus frenatus) culture, fish larvae (0.18 ± 0.014 g) were stocked in concrete tanks and cultured for three months (18 February- 18 May, 2007) according to six treatment regimes: three live food regimes where fish were stocked at 0.3 fish/l (LF1); 0.5 fish/l (LF2); and 1.0 fish/l (LF3); and three traditional (pelleted) diet regimes where fish were stocked at 0.3 fish/l (TD1); 0.5 fish/l (TD2); and 1.0 fish/l (TD3). Exogenous plankton were introduced in the live food tanks. There were three replicates for each treatment, where the fish were fed daily slightly in excess of satiation to eliminate the possibility of food supply being a limiting factor to growth. Values of dissolved oxygen were highest in LF1 treatment, followed by LF2, TD1, LF3, TD2 and TD3 (p<0.05). Average bicarbonate alkalinity, phosphate, nitrate, nitrite, and ammonium nitrogen were significantly higher (p<0.05) in TD2 and TD3, compared to other treatments. Under any particular diet regime, maximum harvest weight and survival rate of rainbow shark was achieved in the treatments with lowest stocking densities (LF1 and TD1), compared to treatments with higher stocking densities (p<0.05). Fish deformities were significantly higher in LF3 and TD3 (p<0.05), compared with treatments with low stocking densities. At any given stocking density, the live food treatment showed better growth and survival, compared to traditional diet treatment. The number of marketable fish above a set size of 4 g was significantly higher (p<0.05) in LF3 (stocking density of 1.0 fish/l), compared to other treatments. In the traditional diet tanks, increase in stocking density resulted in production loss as very few (17.97% in TD2) or none (0% in TD3) of the fish produced in these treatments could be marketed. Introduction of exogenous plankton as food allowed for increased stocking density for intensive rearing of rainbow shark.